POSTSCRIPT TO PART I - Parsons, Charles (From Kant to Husserl, 2012)
“Arithmetic and the Categories” (Essay 2) was written just as a period of impressive growth in the study of Kant’s philosophy of mathematics was beginning. This beginning is marked by the early writings on the subject of Michael Friedman.¹ He has continued to contribute up to the present day. One of his major contributions was to integrate the study of Kant on mathematics with that of his philosophy of physical science. His writings also stimulated work by a younger generation of scholars.² Some reaction to this body of work is called for in the present reprinting. I will concentrate, however,